Information security governance model to enhance zakat information management in Malaysian zakat institutions - Sulaiman H.; Jamil N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Behavioral research; Mobile security; Security of data; Transparency; goal congruence; governance; Information asymmetry; security; trustee; zakat; Information management